Incidence and predictors of mortality among low birth weight neonates in the first week of life admitted to the neonatal intensive care unit in Northwestern Ethiopia comprehensive specialized hospitals, 2022. Multi-center institution-based retrospective follow-up study - Wubet Tazeb Wondie; Kassaye Ahmed Zeleke; Chalachew Adugna Wubneh (BMC, 2023)
Abstract Background Globally, a high number of neonatal mortalities occurs in the first week of life, particularly among low birth weight neonates in low-income countries, including Ethiopia. However, there is limited evidence on the early neonatal mortality of low-birth-weight neonates in Ethiopia. Therefore, this study aimed to assess incidence and predictors of mortality among low-birth-weight neonates in their first week of life admitted to the neonatal intensive care unit in Northwestern Ethiopia Comprehensive Specialized Hospitals, 2022. Methods A multi-center retrospective follow-up study was conducted from March 21, 2020 to March 1, 2022, among 761 early neonates with low birth weight admitted in Northwestern Ethiopia Comprehensive Specialized Hospitals. The study participants were selected using simple random sampling technique. Data were collected using a data abstraction checklist ,and checked for completeness and entered into EPI data version 4.6, then exported to STATA 14 for analysis. Kaplan Meier failure curve and log-rank test were used to estimate and compare the probability of death. Both bivariable and multivariable Weibull regression models were fitted to identify predictors of mortality. Finally, a hazard ratio with 95% CI was computed, and variables having a p-value < 0.05 were considered as a significant predictor of mortality. Results The incidence of mortality among low birth weight neonates in their first week of life was 75.63 per 1000 neonate day observation (95% CI: 66.76-85.67), preeclampsia (AHR = 1.77;95% CI:1.32-2.36s), perinatal asphyxia (AHR = 1.64; 95% CI:1.14-2.36), respiratory distress syndrome (AHR = 1.76 95% CI;1.31-2.34), necrotizing enterocolitis (AHR = 2.78 95% CI;1.79-4.32), prematurity (AHR = 1.86; 95% CI:1.30-2.67), and birth weight < 1000gram (AHR = 3.13;95% CI: 1.91-5.12) and 1000-1499 gram (AHR = 1.99; 95% CI:1.47-2.68) were predictors. Conclusion The incidence of early neonatal mortality in low birth weight neonates was incredibly higher than the overall early neonatal mortality in Northwest Ethiopia (Amhara region). Preeclampsia, perinatal asphyxia, respiratory distress syndrome, necrotizing enterocolitis, prematurity, and birth weight were predictors of mortality. Therefore, stakeholders shall give early identification and emphasis on preventable and treatable predictors. Furthermore, the health care provider shall give education about the importance of breastfeeding, and Antenatal and postnatal care.